Perbandingan Nilai DCP (Dynamic Cone Penetrometer) Laboratorium dengan CBR (California Bearing Ratio) Laboratorium - Fahreza, Rego; Mulyati, Ely; Dewi, Anggi Purnama Sari (Universitas Batanghari Jambi, 2025)
This study aims to compare the Dynamic Cone Penetrometer (DCP) value with the laboratory California Bearing Ratio (CBR) value on soil classified as SC according to USCS and A-2-6 according to AASHTO. Soil samples were taken from the area of the Balai Besar Pelaksanaan Jalan Nasional (BBPJN) South Sumatra at a depth of ±60 cm in three test points. The laboratory tests included natural moisture content, specific gravity, Atterberg limits, sieve analysis, and standard Proctor compaction. The compaction test results showed an optimum moisture content of 18.06% and a maximum dry density of 1.70 g/cm³. The CBR values were obtained from laboratory testing, while the DCP values were measured through dynamic cone penetration on the same samples. Correlation analysis using four methods (PUPR, ASTM, Kleyn, and Zumrawi) indicated varying results. The PUPR method produced the most consistent estimates compared to laboratory data, while ASTM D6951-03 achieved the highest coefficient of determination (R^2 = 0.9743). The Kleyn method remained applicable though less accurate, whereas the Zumrawi method showed significant deviations and was unsuitable for the soil conditions in this study. These findings confirm that the DCP test can serve as a rapid and efficient alternative for estimating CBR values of subgrade soils with similar characteristics.